Strategies for Overcoming Product Certification Challenges Faced by Food Manufacturing Small and Medium Enterprises in Tanzania - Matindiko, Ritha; Bulemo, Peresi Majura (Tanzania Journal of Engineering and Technology, 2025)
<span style="color: #333333; font-family: Montserrat, Helvetica, Arial, sans-serif; font-size: 16px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;">Small and Medium-sized Enterprises SMEs in Tanzania face significant regulatory challenges within bureaucratic, costly, and<br style="box-sizing: border-box; color: #333333; font-family: Montserrat, Helvetica, Arial, sans-serif; font-size: 16px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;"><span style="color: #333333; font-family: Montserrat, Helvetica, Arial, sans-serif; font-size: 16px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;">centralized environments. These challenges contribute to an increase in unregistered enterprises and substandard products in the market. This study aimed to address the challenges SMEs encounter in obtaining product certification to improve their product quality and market competitiveness. A mixed-methods approach was employed, combining qualitative and quantitative research through surveys, interviews, and document analysis, with respondents from the Tanzania Bureau of Standards TBS, Small Industries Development Organization SIDO, and SMEs in the food manufacturing sector. Data analysis was conducted using SPSS and JASP. Findings revealed that SMEs face challenges impacting market access 21.4, product quality 23.6, safety 19.9, and competitiveness 18.8. Confirmatory Factor Analysis CFA identified key latent variables influencing these factors, including market access 0.5, product quality 0.7, safety 0.4, and competitiveness 0.. Additionally, the Delphi technique was employed to validate the findings, involving 10 knowledgeable and experienced respondents in the product certification process. To mitigate challenges hindering product certification among SMEs, several strategies are proposed, including improving certification information dissemination through<span style="color: #333333; font-family: Montserrat, Helvetica, Arial, sans-serif; font-size: 16px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;">user friendly, multilingual online platforms, offering technical expertise, advocating for technology subsidies, and providing financial<span style="color: #333333; font-family: Montserrat, Helvetica, Arial, sans-serif; font-size: 16px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;">support through government certification grants.